PENGARUH DISIPLIN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA PEGAWAI DINAS PERTANIAN KABUPATEN KONAWE - Irham Natsir K (Jurnal Manajemen Lakidende: Economic & Business, 2020)
The purpose of this study was to determine the Effect of Work Discipline and Education Level on Employee Performance at the Agriculture Service Office of Konawe Regency. Operationally the work discipline variable is measured by three indicators, the education level variable is measured by four indicators and the performance variable is measured by four indicators. The population in this study amounted to 26 employees of the Konawe District agriculture office, with the sampling technique using saturated sample techniques. Data taken from questionnaires distributed to respondents. Analysis of the data used in this study are: multiple regression test, t test, F test, normality test and the determinant coefficient test. The results of the study concluded, that (1). Work discipline and education level simultaneously have positive and significant effect on employee performance, this is indicated by the acquisition of F test value of 0,000 <0.05. (2). Work discipline has a positive and significant effect on employee performance as indicated by the acquisition of t-test (partial) 0.032 <0.05. (3) education level partially has a positive and significant effect on employee performance, this is indicated by the value of Sig.0,021 <0.05